2016
DOI: 10.1021/jacs.6b07182
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Signatures of Electronic Properties in Oxidized Water: Unraveling the Anomalous Spectrum of the Water Dimer Cation

Abstract: The water dimer cation, (H 2 O) 2 + , has long served as a prototypical reference system for water oxidation chemistry. In spite of this status, a definitive explanation for the anomalousand dominantfeatures in the experimental vibrational spectrum [Gardenier, G. H.; McCoy, A. B. J. Phys. Chem. A, 2009, 113, 4772−4779] has not been determined, and harmonic analyses qualitatively fail to reproduce these features. In this computational study, accurate quantum chemistry methods are combined with a fully coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 117 publications
(138 reference statements)
4
21
0
Order By: Relevance
“…We have optimized two cationic dimers, in hemibonded (HB) and proton‐transferred (PT) forms, at the DF‐OLCCD/aDZ level. These structures are in agreement with the previous theoretical studies . Relative energies of the dimers, at the CBS level, are reported in Table .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We have optimized two cationic dimers, in hemibonded (HB) and proton‐transferred (PT) forms, at the DF‐OLCCD/aDZ level. These structures are in agreement with the previous theoretical studies . Relative energies of the dimers, at the CBS level, are reported in Table .…”
Section: Resultssupporting
confidence: 91%
“…Relative energies of cationic dimer clusters (Table ) at CCSD(T)/CBS level differ as much as 8.7 kcal mol −1 , which is in very good agreement with the value of 8.8 kcal mol −1 reported by Schaefer and coworkers at the CCSD(T)/aug‐cc‐pVQZ level. As it was discussed in previous studies, the PT form (dimer‐2) is significantly more stable than the HB form (dimer‐1). Mean absolute errors (MAEs) of other considered methods with respect to CCSD(T) are 0.6 (MP2), 1.9 (MP3), 0.2 (DF‐OLCCD), and 1.2 (CCSD) kcal mol −1 .…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…The detailed, inner-sphere redox mechanisms 10 of many of these catalysts remain experimental challenges, however, which hampers further catalyst development. Recently, our research group has provided detailed computational analyses of the first oxidation step in bare water, including structures and spectra of (H 2 O) 2 + , 11 (H 2 O) 1−5 + , 12 and (H 2 O) 6−21 + . 13 In addition to explaining the unique vibrational signatures of the initially formed ion-radical contact pair (H 3 O + •••OH • ), these studies and others 14−17 demonstrated a propensity for ion-radical pair separation for n ≥ 5, which continues through n = 21 (and likely beyond 18 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gauss-Hermite quadrature was used for evaluation of the potential energy and dipole matrix elements. [124][125][126] The theoretical methods used in these calculations included harmonic normal-mode analysis; localmode vibrational self-consistent field theory (VSCF); 127,128 second-order, local-mode vibrational degenerate perturbation theory (VDPT2) 129 on VSCF states; the local-monomer approximation (LMon); [130][131][132][133][134][135][136][137] and a perturbatively corrected local-monomer model (cLMon) that included twomode, cross-monomer couplings. 138 Across all models, the small system sizes allowed ten quanta of excitation to be included along each mode.…”
Section: Vibrational Modelsmentioning
confidence: 99%